The Pseudo-Eutectic Microstructure and Enhanced Properties in Laser-Cladded Hypereutectic Ti–20%Si Coatings - Hui Zhang; Zhonghong Zhang; T. M. Yue (Metals, 2017)
Ti5Si3 is an attractive light weight reinforcement phase in hypereutectic Ti–Si-based alloys, however, the proeutectic Ti5Si3 phase is brittle and is easily coarsened when the alloy is prepared under normal solidification conditions, thereby limiting its engineering applications in the aviation and biological industries. In this study, a hypereutectic Ti–20%Si coating with a pseudo-eutectic α-Ti + Ti5Si3 microstructure was successfully fabricated on a commercially available Ti alloy by laser cladding under non-equilibrium rapid solidification conditions. The fine, rod-like and well-dispersed eutectic Ti5Si3 phase, without the primary Ti5Si3 phase, that was produced resulted in a considerable improvement in hardness, corrosion resistance, and fracture resistance when compared to the same compositional alloy prepared by the conventional arc melting technique.